Effect of Palm Kernel Cake Based Diet on Libido and Semen Quality of Malin X Santa-Ines Lambs - Gebretsadik, Zelealem Tesfay (2004)
A study was conducted for six months at the farm of the Department of Animal Science, Universiti Putra Malaysia (UPM), Serdang, Selangor (3' 00' N, 101' 42' E) to investigate the effect of palm kernel cake based diet on serving capacity and semen quality of Malin x Santa-lnes crossbred ram lambs. Twenty Malin x Santa-lnes crossbred ram lambs were randomly assigned into three dietary treatments namely (TI) 60% Palm kernel cake + 40% oil palm frond, (T2) 60% Palm kernel cake + 40% oil palm frond supplemented with 23 mgkg dry matter of molybdenum as ammonium molybdate ((NH4)6M07024.4H20a)n d 600mglkg dry matter of Sulfur as sodium sulphate (Na2S04) and (T3) control; 60% concentrate of corn-soybean mix + 40% oil iii palm frond. There was no significant difference (p>0.05) among the rams for the three dietary treatments for libido or mating behavior. All rams reached their optimum mating behavior (number of ejaculation = 6.7f1.3 and mating efficiency = 0.43kO.01) after the second month of the experiment. It was also found that there was no significant difference (p>0.05) for all the semen quality parameters among the rams under the three dietary treatments. Rams in all dietary treatments produced good semen and their sperm characteristics were within the ranges for good rams (semen volume = 0.7-2.0 ml; sperm concentration =2-5 X lo9 celldml; sperm motility > 80%; percentage of abnormal morphology 4 5%). Although there was a significant difference on the level of copper (Cu) accumulated in the liver (pc0.01) and testis (p<0.05), with highest values in rams under T1 (1089 + 189 ppm and 0.63 f 0.18 ppm, respectively), there was no symptom of toxicity observed in the rams. Therefore, it was concluded that PKC has no negative effect on serving capacity and semen quality of Malin x Santa-lnes crossbred sheep, at least for six months of the feeding period. It was also concluded that supplementing 23 mglkg dry matter of Molybdenum and 600 mgkg dry matter Sulphur to sheep fed on PKC based diet helps to protect Cu accumulation in the plasma, liver and testis of rams without negative effect on their reproductive capacity and semen quality. Even though higher serum testosterone was found in rams under diets T1 and T2 compared to T3, this did not reflect the actual reproductive level and sperm quality. Hence, it was concluded that serum testosterone level might not be a good indicator of reproductive performance of rams when blood samples are taken from conscious animals.